The memory hole : the U.S. history curriculum under siege - Fischer, Fritz (Emerald Publishing Limited : Information Age Publishing, Inc., 2014)
The U.S. history curriculum is under attack. Politicians, political analysts, and ideologues seek to wipe clean the slate of the American past and replace it with one of their own invention. The basis for this new narrative comes from political beliefs of the present, rather than any systematic examination of the past. These anti-historians campaign to insert their version of American history into the nation's classrooms, hoping to begin a process that will forever transform our understanding of America's past.The Memory Hole examines five central topics in the US history curriculum, showing how anti-historians of both the left and right seek to distort these topics and insert a refashioned story in America's classrooms. Ignoring facts, refashioning other facts and pretending that there are no rules in the telling of history, these re-interpreters of the past place the minds of America's young people in danger. The beleaguered hero of this book is the discipline of History, and The Memory Hole shows how the history curriculum should adhere to history's habits of mind that require complex, sophisticated and subtle thinking about the past. History and social studies teachers, students of history and all those who care about the deep and enduring value of history will value this book and its conclusions.
Keywords: Curriculum planning -- United States -- History.; Education -- Curricula -- United States -- History.; United States -- Historiography.; United States -- History -- Study and teaching.; Education -- Curricula.; Curriculum planning and development.; elektronické knihy; electronic books